S22: Tools and Methods for Physical Activity Interventions – Examples From Projects Among Older Adults and Patient Populations (Baltic Journal of Sport and Health Sciences, 2026)
Targeted interventions for physical activity (PA) promotion require tools for identifying the individuals or groups who would benefit most from the PA intervention and understanding determinants of their behaviour. This symposium presents various tools and methods that have been applied to PA interventions among older adults and patient populations. Increasing knowledge of factors for successful PA interventions among these vulnerable groups enhances the sustainable development goals of ‘Good health and wellbeing (3)’ and ‘Reduced inequalities (10)’.In the first presentation, we hear about the CDC’s STEADI Algorithm, which is a coordinated approach to fall prevention, including the identification of at-risk individuals and addressing risk factors. The speaker presents results from their study, which evaluated the integration of the STEADI Algorithm into Slovenia’s primary healthcare system and the results of the vAdBeCeDa movement programme.In the second presentation, we learn about digital mobility outcomes (DMOs) to assess real-world mobility by targeting walking activity (amount, pattern) and gait (pace, rhythm, variability). The DMOs are developed in the European Mobilise-D project, for which participants were recruited from 17 sites in 10 countries. The speaker presents their results from the validation of the DMOs in patient populations.The third presentation is about mobile health (mHealth) technologies in PA interventions. The speaker shows results of their systematic review and meta-analysis, in which they evaluated the effectiveness of various types of mHealth tools in improving physical health, quality of life, cognitive function, and mental wellbeing among community-dwelling older adults aged 65 and above.The fourth presentation introduces how systems mapping can be applied to identify key determinants of participation in a PA programme. The speaker explains how various analytical methods are applied to produce a comprehensive view of the lived experiences and opinions of older adults across Wales on participation in the 60+ Active Leisure Scheme.The symposium aims to provide the participants with new ideas on tools and methods to apply to interventions. There will be room for discussion and more specific questions. Moreover, the symposium offers possibilities to network and foster collaboration.